PEREMPUAN DALAM MASA REVOLUSI DALAM CERPEN S. RUKIAH: SEBUAH PEMBACAAN GINOKRITIK (Women during Revolution Time in S. Rukiah’s Short Story: A Gynocritical Reading) - Oktarina, Dwi; Tjahjandari, Lily Tjahjandari; Warsono, Sunu (Kantor Bahasa Provinsi Sulawesi Tenggara, 2024)
The revolutionary period is described as an important chapter in modern Indonesian history. At this time, self-awareness as an independent nation was formed within the Indonesian people. As one of the women writers during the revolutionary era, Rukiah’s thoughts made enthusiasm within the framework of liberating women. This research seeks to reveal Rukiah's position as a woman writer by using the women as a writer or ginocritic approach in the short stories